“Oh what a world”: Queer Masculinities, the musical construction of a reparative cultural historiography, and the music of Rufus Wainwright - Schwandt, Kevin C. (Université du Minnesota, 2010)
Throughout his ascendancy in fame and cultural visibility, singer/songwriter and gay pop icon Rufus Wainwright's output has been consistently related, by scholars and critics alike, to camp aesthetics, modes of artistic expression typically understood as emerging from queer communities, particularly certain gay male populations, but ones whose political potential is highly contested. Traditional conceptions of camp, as most famously articulated by Susan Sontag in the 1960s, emphasize style over content, necessarily rendering it politically-disengaged. However, scholars have vehemently challenged conceptions like Sontag's, in order to reclaim camp as a potent means to facilitate queer world-making and a powerful resistance to heteronormativity. I examine Wainwright's image and music in order to theorize a new queer interpretive listening position. Specifically, I draw upon the literary perspective of “reparative reading,” articulated by Eve Kosofsky Sedgwick in opposition to what she describes as “paranoid reading,” to propose a uniquely queer approach to musical and cultural historiography, exemplified by Wainwright's music. Much of the current queer musicology focuses on lost histories, systematic marginalization, and the commoditization of queer identities. While such approaches have produced important insights, thorough examination of the relationships between queer cultural products and their queer reception has proven elusive. This project suggests a unique approach to understanding the musical construction of a specific kind of queer masculinity, one which combines authorial creation with reparative conceptions of reception, in order to theorize a uniquely gay male interpretive position. When viewed through a theoretical lens combining politically-potent conceptions of camp performativity with a reparative reading position, Wainwright's music strikingly enacts Philip Brett's call to claim, not historical evidence, but the right of interpretation, emerging as an act of resistance via the reclamation and consolidation of a queer interpretive authority. In this way, Wainwright articulates both a rupture in the history of queer masculinity and a powerful means of resistance to the often-exclusionary relationships between literary, musical, and artistic objects and the heteronormative cultural systems in which they are created.
Keywords: 2000 à aujourd'hui; 2000-2009; DIG; LGBTQIA2+; approches et analyses; arts; culture populaire; discipline; historiographie; hétérosexisme; identités LGBTQIA2+; masculinité; musique; mémoires/thèses; périodes historiques; queer; ressource en ligne; résistance; systèmes d'oppressions; thématiques

Être compositeur aujourd'hui : entretien de Sophie Stévance avec Isabelle Panneton - Stévance, Sophie (Composer au XXIe siècle: pratiques, philosophies, langages et analyses, 2010)
Keywords: 2000 à aujourd'hui; 2000-2009; DIG; arts; discipline; femmes* artistes; musique; périodes historiques; ressource en ligne

Quelle place pour les femmes dans la création musicale au XXIe siècle ? - Stévance, Sophie (Composer au XXIe siècle. Pratiques, philosophies, langages et analyses, 2010)
Keywords: 2000 à aujourd'hui; 2000-2009; DIG; arts; discipline; femmes* artistes; musique; périodes historiques